Effect of Variations in Tooth Flank Form Among Teeth on Gear Vibration and an Sensory Evaluation Method Using Potential Gear Noise - Edzrol Niza MOHAMAD; Masaharu KOMORI; Shigeki MATSUMURA; Chanat RATANASUMAWONG; Masanori YAMASHITA; Takushi NOMURA; Haruo HOUJOH; Aizoh KUBO (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2010)
Since variations in tooth flank form among the teeth of a gear are one of the primary causes of noise and vibration in gear systems, the effects of these variations should be analyzed. In the present paper, a simulation program is proposed in which variations in tooth flank form among the teeth of a gear are considered. The effect of different surface finish methods on gear vibration was analyzed using the developed program. The effects of periodic change of profile and helix slope deviation on the vibrational excitation were also examined. The concept of potential gear noise, which is a noise to express directly the effect of tooth flank form of gear on the gear noise, is proposed and a sensory evaluation method is also proposed to evaluate sound level, noise quality and noise uncomfortness. Sensory evaluation result shows that, even if the gears manufactured by different grinding methods have the same tooth flank form macroscopically, they make a large difference in terms of noise quality or uncomfortness because microscopically, the tooth flank form is different among grinding methods. It can be concluded that the proposed sensory evaluation method of potential gear noise could enable gear designers to experience directly the effect of tooth flank form on the noise quality.